2017
DOI: 10.15578/jra.11.3.2016.281-289
|View full text |Cite
|
Sign up to set email alerts
|

AKTIVITAS ANTIBAKTERI PENYEBAB VIBRIOSIS TERHADAP UDANG WINDU DARI EKSTRAK HERBAL MANGROVE Sonneratia alba DAN Bruguiera gymnorrhiza

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui aktivitas antibakteri dari ekstrak herbal mangrove Sonneratia alba dan Bruguiera gymnorrhiza terhadap penyebab penyakit vibriosis pada udang windu. Daun mangrove S. alba dan B. gymnorrhiza masing-masing diambil dari Kabupaten Maros dan Pangkep. Sampel daun dikeringanginkan selama dua minggu, ditepungkan, diekstraksi dengan metanol 80%, dan dievaporasi. Rendemen yang diperoleh dipartisi menggunakan dua jenis pelarut yaitu butanol dan dietileter. Uji bioassay dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
2
4
0
1
Order By: Relevance
“…Bacteria produced from V. harveyi bacteria weakened with 1% formalin is proven to increase the cellular defenses of tiger shrimp so that they can be used as immunostimulants in shrimp [5]. Similar to this study, it was found that formalin-inactivated Vibrio administered orally to Fenneropenaeus merguiensis postlarvae induced protection against V. anguillarum and V. harveyi infections [6].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Bacteria produced from V. harveyi bacteria weakened with 1% formalin is proven to increase the cellular defenses of tiger shrimp so that they can be used as immunostimulants in shrimp [5]. Similar to this study, it was found that formalin-inactivated Vibrio administered orally to Fenneropenaeus merguiensis postlarvae induced protection against V. anguillarum and V. harveyi infections [6].…”
Section: Introductionsupporting
confidence: 78%
“…As part of the state demand, shrimp consumers currently emphasize food safety, which requires the importing state to produce shrimp that is free from harmful ingredients such as antibiotics. Alternative disease prevention in shrimp culture that is environmentally friendly has been widely developed, including the use of probiotics, bacterial vaccines (bacterin) [1], and from natural products such as mangrove herbs [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted both locally and internationally to determine the potential of mangrove plant extract as an alternative to disease prevention in the shrimp farming. Several research results have been reported both from within the country and from abroad related to the use of mangrove herbs as an alternative to preventing bacterial and viral diseases in tiger shrimp culture [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the utilization of methanol, ethanol, butanol, and other chemical solvents for mangrove extraction have been carried out. Muliani et al, 2016 [28], reported that diethyl ether and methanol extract of S. alba and butanol extract of B. gymnorrhiza have relatively strong antibacterials. In addition to having antibacterial, both types of mangroves are suspected to have anti-WSSV.…”
Section: Introductionmentioning
confidence: 99%
“…penyebab penyakit vibriosis belum pernah dilakukan. Sejauh ini penelitian yang pernah dilakukan untuk menanggulangi penyakit vibriosis, berkisar pada penggunaan ekstrak Sonneratia alba, Avicennia alba, daun Rhizophora mucronata, dan daun jeruju (Suciati et al, 2012;Saptiani et al, 2013;Muliani et al, 2016;Farida et al, 2020).…”
unclassified